Transformational and taxic homology revisited. (28th March 2014) - Brower, Andrew V. Z.
Abstract Usages and meanings of the terms "taxic" and "transformational homology" are reviewed from 1982 to the present. While "taxic homology" has been relatively invariant in its connotation, "transformational homology" as employed by different authors refers to at least three different concepts. This has resulted in confusion.